KONDISI UMUM KAWASAN PERBATASAN DAN STRATEGI ALTERNATIF PENGEMBANGAN WILAYAH KALIMANTAN UTARA - Tri Widodo W. Utomo (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
The dispute on Ambalat Block between Indonesia and Malaysia has encouragedgovernment institutions to pay more vigilance on the promotion of developmentprograms of border areas. There is a shift of paradigm posing border-areas as the‘frontyard’ instead of ‘backyard’. It implies that efforts on promoting borderdevelopment along North Kalimantan region call for an an emergency policy orcatch-up strategy. This comprises endeavors for establishing specific institution,providing ample amount of funds, and designing an integrated action plan on thehastening of border development. This paper portrays some essential dimensions ofborder areas such as general description and problems of border areas, the nature of Ambalat conflict, legal framework of border areas, and recommended strategies to redevelop the North Kalimantan region.